ROLE OF INSTRUCTIONAL MATERIALS IN IMPROVING PUPILS WITH DYSLEXIA IN PUBLIC PRIMARY SCHOOLS IN EKWUSIGO LGA OF ANAMBRA STATE - Udeagbala, Ikechukwu R.; Onwuka, Lilian N.; Ugwude, Doris I. (Journal of Early Childhood and Primary Education, 2020)
The study was conducted to determine the role of instructional materials in improving pupils with dyslexia in public primary schools in Ekwusigo L.G.A of Anambra state. Two research questions guided the study. Descriptive survey design was adopted to carry out the study. The population of the study consisted of 235 public primary school teachers from 38 public schools in Ekwusigo L.G.A. Simple random sampling was used to select 100 public primary school teachers from 10 schools randomly selected from the 38 public primary schools in the study area. The instrument used for data collection was a 17 item structured questionnaire developed by the researchers titled â€œInstructional Materials for Improving Pupils with Dyslexia (IMIPD)â€. The instrument was validated by three experts. Cronbach Alpha was to determine the reliability of the instrument and the overall reliability of 0.70 was obtained. Mean was used for data analysis. The findings, among others, revealed that instructional materials help dyslexic pupils to develop interest and participate in activities, improve understanding and retention. The findings also revealed that lack of fund to make purchase, inability of teacher to improvise and make suitable selection of instructional materials among others are factors that are against the use of instructional materials in improving dyslexic pupils. Based on the findings, it was recommended, among others, that teachers should always use suitable instructional materials that address the need of dyslexic children while teaching and state government and school authority should aid in providing instructional materials in schools.